Implementation of legal abortion in Nepal: a model for rapid scale-up of high-quality care - Samandari Ghazaleh; Wolf Merrill; Basnett Indira; Hyman Alyson; Andersen Kathryn (BMC, 2012)
Abstract Unsafe abortion's significant contribution to maternal mortality and morbidity was a critical factor leading to liberalization of Nepal's restrictive abortion law in 2002. Careful, comprehensive planning among a range of multisectoral stakeholders, led by Nepal's Ministry of Health and Population, enabled the country subsequently to introduce and scale up safe abortion services in a remarkably short timeframe. This paper examines factors that contributed to rapid, successful implementation of legal abortion in this mountainous republic, including deliberate attention to the key areas of policy, health system capacity, equipment and supplies, and information dissemination. Important elements of this successful model of scaling up safe legal abortion include: the pre-existence of postabortion care services, through which health-care providers were already familiar with the main clinical technique for safe abortion; government leadership in coordinating complementary contributions from a wide range of public- and private-sector actors; reliance on public-health evidence in formulating policies governing abortion provision, which led to the embrace of medical abortion and authorization of midlevel providers as key strategies for decentralizing care; and integration of abortion care into existing Safe Motherhood and the broader health system. While challenges remain in ensuring that all Nepali women can readily exercise their legal right to early pregnancy termination, the national safe abortion program has already yielded strong positive results. Nepal's experience making high-quality abortion care widely accessible in a short period of time offers important lessons for other countries seeking to reduce maternal mortality and morbidity from unsafe abortion and to achieve Millennium Development Goals.